The systems and signs of political militants in/of Brazilian nursing - Deybson Borba de Almeida; Gilberto Tadeu Reis da Silva; Genival Fernandes de Freitas; Nívia Vanessa Carneiro dos Santos; Igor Ferreira Borba de Almeida; Deivison Oliveira da Silva
ABSTRACT Objectives: to analyze the systems and signs in the constitution of militant nurses. Methods: a historical and qualitative research based on oral history carried out with 11 nurses who had been working in the professional field since 1980. Data collected from semi-structured interviews were organized into NVivo software 10, being analyzed through dialectical hermeneutics. Results: systems and signs are systems that allow us to use senses, symbols or meaning to objectify and subjectivate the subject. The revealed senses were categorized and divided into improper, religious, heroic, communist, and socially involved. Conclusions: militancy signs are convergent with what is put in national and international literature. The difference found was in the heroic sense and implicated with the social. Militant is almost never associated with positive aspects. An individual who builds himself as a political being empowers himself as a social being, making knowledge of power, generating a break in traditional models.